2021
DOI: 10.1007/s10456-021-09788-4
|View full text |Cite
|
Sign up to set email alerts
|

The endosomal RIN2/Rab5C machinery prevents VEGFR2 degradation to control gene expression and tip cell identity during angiogenesis

Abstract: Sprouting angiogenesis is key to many pathophysiological conditions, and is strongly regulated by vascular endothelial growth factor (VEGF) signaling through VEGF receptor 2 (VEGFR2). Here we report that the early endosomal GTPase Rab5C and its activator RIN2 prevent lysosomal routing and degradation of VEGF-bound, internalized VEGFR2 in human endothelial cells. Stabilization of endosomal VEGFR2 levels by RIN2/Rab5C is crucial for VEGF signaling through the ERK and PI3-K pathways, the expression of immediate V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…ZEB2 can trigger the induction of genes associated with epithelial–mesenchymal transition [ 73 ], activate the Wnt/beta-catenin pathway [ 74 ], and regulate invasion and metastasis [ 72 ]. Endosomal RAB5C was reported to prevent VEGFR2 degradation during angiogenesis [ 75 ], regulate focal adhesion-mediated cell migration [ 76 ], and enhance resistance to ionizing radiation [ 77 ]. DUSP6, a member of the MAPK phosphatase family, is highly expressed in PTC and plays a pro-oncogenic role in thyroid tumorigenesis by regulating the ERK1/2 pathway, cell proliferation, and invasiveness [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZEB2 can trigger the induction of genes associated with epithelial–mesenchymal transition [ 73 ], activate the Wnt/beta-catenin pathway [ 74 ], and regulate invasion and metastasis [ 72 ]. Endosomal RAB5C was reported to prevent VEGFR2 degradation during angiogenesis [ 75 ], regulate focal adhesion-mediated cell migration [ 76 ], and enhance resistance to ionizing radiation [ 77 ]. DUSP6, a member of the MAPK phosphatase family, is highly expressed in PTC and plays a pro-oncogenic role in thyroid tumorigenesis by regulating the ERK1/2 pathway, cell proliferation, and invasiveness [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs. Angiogenesis is strongly regulated by VEGF signaling through VEGF receptors such as VFGFR2 [32]. Overexpression of HSPA12A in HUVECs for 24 h significantly increased VEGF expression compared to the NC group (Figures 4(a) and 4(b)).…”
Section: Hspa12a Upregulates Angiogenic Gene Expression Inmentioning
confidence: 96%
“…Thereafter, the receptor is plugged into a recycling holding pattern, being cyclically internalized and inserted back into the membrane [ 2 ]. Upon ligand binding, VEGFR2 is endocytosed and degraded via the lysosome [ 3 ]. In this example, it is obvious that alterations in any trafficking step of an important protein such as VEGFR2 would have profound effects on blood vessel function independent of transcriptional activity.…”
Section: Trafficking and Rab Gtpase Proteinsmentioning
confidence: 99%
“…In the absence of RabEP2, Rab4-positive vesicles were diverted to a Rab7 lysosomal pathway, significantly attenuating VEGF signaling [ 41 ]. It was also reported that Rab5c partners with RIN2 to delay lysosomal degradation to increase downstream VEGFR2 signaling [ 3 ]. In this article, loss of RIN2 or Rab5c-mediated endosomal stabilization blunted VEGFR2 signaling of Akt and ERK leading to defects in sprouting parameters in culture and zebrafish blood vessel development.…”
Section: Sprouting Angiogenesismentioning
confidence: 99%